2023
DOI: 10.1182/bloodadvances.2022009577
|View full text |Cite
|
Sign up to set email alerts
|

Survival after cancer-related venous thrombosis: the Scandinavian Thrombosis and Cancer Study

Abstract: Cancer patients have an increased risk of developing venous thromboembolism (VTE) and this combination is reported to result in poorer survival compared to cancer alone. The aim of this study was to investigate the impact of VTE on survival of cancer patients in a general population. The Scandinavian Thrombosis and Cancer (STAC) cohort, a population-based cohort including 144,952 subjects without previous VTE or cancer was used. During follow-up, cancer and VTE incidences were registered. 'Cancer-related VTE' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…VTE is a significant independent predictor of early mortality in patients with cancer of all stages and types. 1,3,810,22 The in-hospital mortality rate in our study was 18%, which is higher than that in other studies (11.36%–16.3%). 10,23,24 However, unlike our study in which all patients had advanced-stage disease and most had a compromised functional status, these previous studies mainly included patients with local or regional disease.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…VTE is a significant independent predictor of early mortality in patients with cancer of all stages and types. 1,3,810,22 The in-hospital mortality rate in our study was 18%, which is higher than that in other studies (11.36%–16.3%). 10,23,24 However, unlike our study in which all patients had advanced-stage disease and most had a compromised functional status, these previous studies mainly included patients with local or regional disease.…”
Section: Discussioncontrasting
confidence: 64%
“… 4 6 The presence of VTE in this population has been associated with a worse prognosis, with an approximately 4-times higher risk of death after an acute thrombotic event. 7 9 Studies have shown that VTE not only impacts the 1-year survival rate but also impacts in-hospital mortality within 7, 14, and 30 days. 8 , 10 Additionally, patients with cancer and VTE have higher rates of hospital admission, bleeding, and recurrence than cancer-free patients with VTE.…”
Section: Introductionmentioning
confidence: 99%
“…Our data are also consistent with those from a recently published analysis from the Scandinavian Thrombosis and Cancer (STAC) cohort, which has indicated a 3.4-fold greater mortality risk in cancer patients with than without venous thromboembolism. 15 However, the study did not report data beyond one year, trends over time, or analyses stratified by timing of venous thromboembolism (i.e., concurrently with a cancer diagnosis or thereafter).…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 However, the majority of existing studies evaluating mortality associated with venous thromboembolism among cancer patients are relatively old, based on small sample sizes or selected populations, or focused on short-term mortality. 10 , 11 , 12 , 13 , 14 , 15 Cancer therapy has evolved tremendously in recent decades with the advent of targeted therapies and immunotherapy, as well as novel cancer screening tools and better diagnostic modalities. 16 , 17 Concurrently with improved cancer outcomes, the one-year venous thromboembolism incidence among cancer patients has increased from 1% to more than 3% in recent decades, which may be the result of ageing of the oncology population, frequent detection of asymptomatic clots on diagnostic or staging scans, and use of prothrombotic cancer therapies.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Moreover, despite the advances in cancer treatment, venous thromboembolism in patients with cancer continues to be associated with increased mortality in contemporary cohorts. 6,7 Machine learning (ML) refers to a specialized field of computer science that leverages algorithms to automatically identify patterns in data and ultimately perform a task. This approach has led to numerous transformative applications in diverse fields from voice recognition to virtual assistants, traffic prediction, financial market analysis and forecasting, fraud/criminal recog-N o n -c o m m e r c i a l u s e o n l y nition and even self-driving vehicles.…”
Section: Introductionmentioning
confidence: 99%